Police officer gender and excessive force complaints: an Australian study - Porter, Louise E. (Policing and society, 2017)
Issues of force and excessive force remain prominent in policing in most jurisdictions. This study addresses the relationship between officer gender and force-related allegations, and adds to the growing literature on women in policing and strategies to reduce police-citizen conflict. The study utilised six years of Queensland police data from 2007/2008 to 2012/2013 involving 4974 force-related complaint files and 11,493 allegations, to explore gender patterns while also considering rank, length of service, age, sub-type of allegation, and complaint outcomes. The main finding was that females made up 26% of employed officers, but only 16% of officers receiving complaints and 15% of officers subject to specific allegations. In addition, females had significantly fewer repeat complaints, fewer single subject officer complaints, and complaints against females reduced more quickly with length of service. The findings support the case for significant benefits from improved female representation in policing. At the same time, the paper includes a number of qualifiers regarding support for female officers and optimal management of use of force training and procedures.